Antioxidant status and sex hormones in women with complex endometrial hyperplasia - Pejić, S; Todorović, A; Stojiljković, V; Pavlović, I; Gavrilović, L; Popović, N; Pajović, S B (Cellular and Molecular Biology, 2016)
Endometrial tissue is under a strong influence of sex hormones. These hormones are considered as developmental factors of endometrial hyperplasia and endometrial cancer. We examined the influence of gonadotropins (follicle-stimulating and luteinizing hormone) and sex hormones (estradiol, progesterone) on oxidant/antioxidant parameters in blood and endometrial tissue of women with complex endometrial hyperplasia. In blood, superoxide dismutase activity was significantly higher in luteal phase and postmenopause compared to the follicular phase. A significant phase-related difference of glutathione peroxidase and glutathione reductase activity was recorded in the endometrium. Both enzymes had lower activity in luteal phase and postmenopause compared to the follicular phase. The linear regression analysis of individual hormonal variables against antioxidant parameters showed negative correlation between glutathione peroxidase activity and gonadotropin concentrations in the endometrium. The regression of hyperplastic to normal endometrium is the purpose of conservative treatment based on administration of progestogens or gonadotropin-releasing hormone analogues. Our findings indicate that gonadotropins influence the antioxidant enzymes activity in women with complex endometrial hyperplasia, which may affect disease development. Further studies are needed to clarify the molecular basis of hormone action on antioxidant system that may potentially initiate a development of treatments based on redox-dependent mechanism.